Nitrogen-tixing and vesicular-arbuscular mycorrhizal symbioses in some tropical legume trees of tribe Mimoseae - Patreze, C. M.; Cordeiro, L. (Elsevier B.V., 2004)
Response to mineral fertilization and inoculation with rhizobia and/or arbuscular mycorrhiza fungi (AMF) of the Anadenanthera colubrina, Mimosa bimucronata and Parapiptadenia rigida (Leguminosae-Mimosoideae) native trees from Brazilian riparian forests, were studied in nursery conditions. Each species was submitted to seven treatments, varying nitrogen and phosphorous fertilization and inoculation with rhizobia (r), mycorrhiza (m) or both (rm): NP, P, P + r, P + rm, N, N + m and N + rm. Results showed that AMF inoculations did not enhance the mycorrhizal colonization, and P uptake was not sufficient to sustain good growth of plants. The level of P mineral added affected negatively the AMF colonization in A. colubrina and M. bimucronata, but not in P. rigida. Native fungi infected the three legume hosts. The absence of mineral N limited growth of A. colubrina and P. rigida, but in M. bimucronata the lack of N was corrected by biological nitrogen fixation. N mineral added inhibited the nodulation, although spontaneous nodulation had occurred in A. colubrina and M. bimucronata. Rhizobia inoculation enhanced the number of nodules, nitrogenase activity and leghemoglobin content of these two species. Thus, the extent of rhizobial and mycorrhizal symbiosis in these species under nursery conditions can affect growth and consequently the post-planting success. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: nitrogen fixation; Mimoseae; Mycorrhiza; rhizobia; Riparian forest; symbiosis